Il cibo come fattore identitario: il lessico culinario nelle cronache di calcio italiane – un’analisi corpus-based - Godzich, Anna; Szpingier, Beata Katarzyna (Studia Romanica Posnaniensia, 2024)
The article examines the role of food in shaping the Italian national identity based on the example of Italian football language in the most-read Italian newspaper entitled “La Gazzetta dello Sport” (www.gazzetta. it). At first, the concept of identity is analyzed and then its particular shades in the case of Italy and the attitude of Italians toward food, its importance and widespread occurrence within the entire country will be discussed. In fact, the food is a factor which seems to be a bonding element for all Italians and a means of expressing the current Italian national identity. The author identifies it as the Italian culinary identity. The phenomenon can be observed in such presently existing Italian culinary terms as cioccolatino, brodino, biscotto, spezzatino, mangiarsi un gol and the like that are used in Italian football news.